PENERAPAN TOGAF ADM UNTUK PERENCANAAN ENTERPRISE ARCHITECTURE SISTEM INFORMASI PADA UPT BKN JAMBI - Putra, Sumpena Adi; Roestam, Rusdianto (Jurnal Manajemen Sistem Informasi, 2020)
Indonesia’s governance to open government is a must do to provide information disclosure to the public. In this case, UPT BKN Jambi as the leading guard has the vision and mission to carry out the staffing service approach to the region area of Jambi province, such as transform business functions towards digitalization, but to realize this, UPT BKN Jambi doesnâ€™t have enterprise architecture documentation yet to be guidelines for realized information systems development based on business functions and user needs. Therefore, it needs a planning to define and identify business needs, data, applications, and technologies that can represent a enterprise architecture. This planning must have steps and methodologies can be used to help analyze organizational unit needs. TOGAF ADM as a method used to develop the planning, designing, implementation, management, and implementation of information system architecture governance. Steps of 4 domains of information system architecture development, namely : business architecture, data architecture, application architecture, and technology architecture are applied to produce blueprint documentation that can be guidelines realized of an integrated information system based on the change and needs of the organizational development forward